Pengujian Empiris Efficient Market Hypothesis (EMH) Dan Capital Assets Pricing Model (CAPM) - Rafrini Amyulianthy; Asriyal Asriyal (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
As indicated, Efficient Market Hypothesis theory played an important role in evolution of accounting research. The conflict between the Efficient Market Hypothesis and hypotheses underlying many accounting prescriptions led to the introduction and popularization of positive theory and methodology in the accounting literature. This paper is to provide a clearer understanding of the factors anomalies encountered by experts during a test of the reliability Efficient Market Hypothesis and Capital Asset Pricing Model (CAPM) theories which proposed by Fama in 1970.